2007
DOI: 10.1167/iovs.06-1207
|View full text |Cite
|
Sign up to set email alerts
|

Anisometropic Amblyopia: Spatial Contrast Sensitivity Deficits in Inferred Magnocellular and Parvocellular Vision

Abstract: Anisometropic amblyopia produces spatial contrast sensitivity losses in inferred PC- and MC-mediated vision, suggesting there may be anomalous processing of MC and PC signals in higher visual areas, including those with orientation and spatial frequency selective cells in the visual cortex. With spatially localized stimuli and a paradigm designed to distinguish between MC and PC vision under conditions that differ only in the interstimulus adaptation, the better eye of the amblyopes was normal or near normal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 56 publications
2
32
0
2
Order By: Relevance
“…Moreover, Maebera et al 8 reported that contrast sensitivity was reduced in amblyopic eyes, while normal eyes were generally normal. Similar to Zele et al 20 , in the present study we detected no significant differences in CSF throughout the spatial frequency range when the normal eyes of microtropic and anisometropic patients were compared with age-matched nomograms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, Maebera et al 8 reported that contrast sensitivity was reduced in amblyopic eyes, while normal eyes were generally normal. Similar to Zele et al 20 , in the present study we detected no significant differences in CSF throughout the spatial frequency range when the normal eyes of microtropic and anisometropic patients were compared with age-matched nomograms.…”
Section: Discussionsupporting
confidence: 92%
“…Chatzistefanou et al 9 also found that the normal eyes of amblyopic patients had abnormal CSF, regardless of whether they had undergone occlusion therapy. In contrast, Zele et al 20 found that the normal eyes of amblyopes had normal values at all spatial frequencies. Moreover, Maebera et al 8 reported that contrast sensitivity was reduced in amblyopic eyes, while normal eyes were generally normal.…”
Section: Discussionmentioning
confidence: 86%
“…In humans, the bulk of the data reports greater deficits in aspects of vision thought to be mediated by the P pathway (deficits for high spatial frequency stimuli: Bradley & Freeman, 1981; Hess & Howell, 1977; Levi & Harwerth, 1977, deficits for red/green chromatic stimuli: Davis, Sloper, Neveu, Hogg, Morgan, & Holder, 2006; Demirci, Gezer, Sezen, Ovali, Demiralp, & Isoglu-Alkoc, 2002; but see Zele, Pokorny, Lee, & Ireland, 2007). Corroborating the human results, studies of visually deprived animals have reported that morphological changes are greater within the P layers, compared to the M layers, of the LGN (Hendrickson et al, 1987; LeVay, Wiesel, & Hubel, 1980 and see von Noorden, Crawford, & Levacy, 1983 for greater P disruption in the LGN of a single human).…”
Section: Discussionmentioning
confidence: 99%
“…During the test interval, a D6 pattern of positive contrast was presented in the center of a pedestal square that had a decremental luminance, with both stimuli presented simultaneously for 45 ms. For both paradigms, the D6 was presented with either a vertical or horizontal orientation, chosen randomly. An adapting field was presented continuously for both paradigms (Zele et al, 2007). by the MC pathway, at least at low frequencies.…”
Section: Spatial Contrast Sensitivitymentioning
confidence: 99%